COMPARISON OF INTERMITTENT BOLUS AND CONTINUOUS INFUSION TECHNIQUES FOR ADMINISTRATION OF ATRACURIUM IN RENAL FAILURE - Madhavi Potnis; Shishir Mehta; Deepak Mistry; Nalini Desai (National Journal of Medical Research, 2012)
Introduction: Atracurium besylate is bisquaternary isoquinolinium compound, a potent non depolarizing muscle relaxant of intermediate duration. Its duration of action appears not to be prolonged in absence of normal renal function. Atracurium lacks cumulative effects and its shorter duration of action and rapid recovery from block suggest that Atracurium may be suitable for continuous intravenous infusion.